Penyimpangan Maksim Kerja Sama dalam Serial Kartu Keluarga - Nisa, Choirun; Satyawati, Made Sri; Putra, Anak Agung Putu (CV. Eduartpia Publisher, 2025)
This research examines the flouting of Grice's cooperative principle in the Indonesian drama series Kartu Keluarga. As the foundation of social interaction, effective communication requires an understanding of pragmatics, particularly how violations of the maxims of quantity, quality, relevance, and manner generate implicatures or implied meanings. The series' central conflict, which narrates the story of a single mother's fictitious marriage, triggers numerous deviant utterances that can potentially lead to misunderstandings. This study aims to identify the forms of maxim violations and analyze the reasons behind them. Using a qualitative narrative approach, dialogue data from the first episode were collected using the non-participatory observation method (SBLC) and transcribed. Data analysis was conducted using referential identity and distributional methods to decipher the implied meanings. The findings are presented descriptively to explain the phenomenon of maxim violation in the context of verbal interaction in electronic media.